2016
DOI: 10.1680/macr.15.00111
|View full text |Cite
|
Sign up to set email alerts
|

Creep and residual properties of cracked macro-synthetic fibre reinforced concretes

Abstract: This study analysed the creep behaviour of five concretes incorporating 0·5% by volume of four macro-synthetic fibres (MSFs) and one steel fibre. After 28 d moist curing, prisms were pre-loaded up to a crack opening of 0·5 mm and held for 90 d in three different environments -ambient laboratory air, seawater at 45°C and air flow at 45°C.Sustained loads were then applied on three specimens from each group while the other prisms remained unloaded.The remaining residual capacity was evaluated by bending tests. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…From comparative studies, flexural creep behavior was found influenced by both the fiber type and the load level [4], in this case by using round panels made of shotcrete which were pre-cracked up to 3.5 mm. It was stated that the fiber type and environmental conditions can affect creep behavior and the residual response of SFRC [18]. Similar creep behavior was observed by using three-and four-point loading configurations [19].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…From comparative studies, flexural creep behavior was found influenced by both the fiber type and the load level [4], in this case by using round panels made of shotcrete which were pre-cracked up to 3.5 mm. It was stated that the fiber type and environmental conditions can affect creep behavior and the residual response of SFRC [18]. Similar creep behavior was observed by using three-and four-point loading configurations [19].…”
Section: Introductionmentioning
confidence: 61%
“…Also, variations in load scheme (threepoint bending tests (3PBT) or four-point bending tests (4PBT)), pre-cracking process, and load level and time period, among others factors, has been carried out. Concerning experimental research on flexural creep behavior, the literature found in international journals reports important contributions from research on steel FRC (SFRC) [2,4,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical behaviour of fibre reinforced concrete (FRC) has been widely studied over the past decades [3], and important advances have been achieved regarding the residual strength characterization and applications of FRC [2]. On the other hand the analysis of flexural creep behaviour of cracked FRC elements is a relatively new topic which has not been entirely researched yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although residual strength parameters are applied in structural design, the knowledge of the long-term behaviour of FRC in cracked conditions is limited to a few reports on the subject [1][2][3]5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%